Volatile fragrances associated with flowers mediate host plant alternation of a polyphagous mirid bug - Pan, Hongsheng; Lu, Yanhui; Xiu, Chunli; Geng, Huihui; Cai, Xiaoming; Sun, Xiaoling; Zhang, Yongjun; Williams, Livy; Wyckhuys, Kris A.G. (Springer, 2015)
Apolygus lucorum (Hemiptera: Miridae) is an important insect pest of cotton and fruit trees in China. The adults prefer host plants at the flowering stage and their populations track flowering plants both spatially and temporally. In this study, we examine whether flower preference of its adults is mediated by plant volatiles and which volatile compositions play an important role in attracting them. In olfactometer tests with 18 key host species, the adults preferred flowering plants over non-flowering plants of each species. Coupled gas chromatography-electroantennography revealed the presence of seven electrophysiologically active compounds from flowering plants. Although the adults responded to all seven synthetic plant volatiles in electroantennography tests, only four (m-xylene, butyl acrylate, butyl propionate and butyl butyrate) elicited positive behavioral responses in Y-tube olfactometer bioassays. The adults were strongly attracted to these four active volatiles in multi-year laboratory and field trials. Our results suggest that these four fragrant volatiles, which are emitted in greater amounts once plants begin to flower, mediate A. lucorum’s preference to flowering host plants. We proved that the use of commonly occurring plant volatiles to recognize a large range of plant species can facilitate host selection and preference of polyphagous insect herbivore.